Peningkatan Kesadaran Perilaku Hidup Bersih dan Sehat (PHBS) Melalui Edukasi Partisipatif pada Siswa MI Tarbiyatussubyan - Widia Ayu Usmilawati; Siti Napfiah; Nok Izatul Yazidah; Yunis Sulistyorini (Universitas Muhammadiyah Banten, 2026)
Clean and Healthy Living Behavior (CHLB) is an important foundation for developing a healthy and productive young generation. This community service program aimed to improve the awareness and understanding of upper-grade students (Grades IV, V, and VI) at MI Tarbiyatussubyan regarding personal hygiene and environmental sanitation. The activity employed a participatory educational approach consisting of interactive lectures, demonstrations of proper handwashing techniques based on World Health Organization (WHO) standards, and simulations on selecting healthy snacks. A total of 65 students participated in the program. Evaluation was conducted using pre-test, post-test, and behavioral observation methods. The results showed an improvement in students’ understanding of clean and healthy living behaviors, with the average score increasing from 60% before the activity to 85% after the intervention. In addition, students demonstrated better handwashing practices and greater awareness of waste management and classroom cleanliness. These findings indicate that interactive and participatory health education is effective in improving students’ knowledge and promoting positive behavioral changes related to clean and healthy living habits in the school environment.